EFEKTIVITAS BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH ANAK DENGAN DEMAM PASCA IMUNISASI DPT PENTABIO - Hasibuan, Wilma; Juni Ekasari, Dian; Roza, Nova (Universitas Batam, 2025)
Basic Health Research 2018, the KIPI rate in Indonesia with high fever was 31.2%, abscess 15.3% and seizures 2.9%. There are 2 ways of treatment that can be done if a child has a fever after DPT, namely pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological treatments is red onion compresses. The content of red onions, including propyl disulfide and propyl metal disulfide, which are volatile, when applied to the body, will allow accelerated heat transfer from the body to the skin. This study aims to determine the effectiveness of red onions in reducing the body temperature of children with fever after DPT Pentabio immunization. The design of this study used a non-equivalent control group with pretest-posttest. The population of all infants and toddlers who received DPT Pentabio immunization at the Meral Health Center UPT in July 2024 was 40 children. Sampling used the accidental sampling technique with inclusion and exclusion criteria. Data analysis used SPSS. The results of the study obtained the average temperature before giving the red onion compress was 38.54 and after giving the red onion compress was 38.34. It can be concluded that red onions are effective in reducing the body temperature of children with fever after DPT Pentabio immunization. The results of this study can provide input in the management of Giving Red Onion Compresses to Reduce the Body Temperature of Children with Fever After Immunization